Physical Education Program Competencies of Higher Education Institutions in Region 10: Enhancing Quality - Miguel, CESAR (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The Physical Education (PE) programs of higher education institutions (HEis) need to be assessed if enhancement efforts are to be responsive and effective. Thus, this study was undertaken to assess whether the physical education programs of HEis in Region 10 have met the minimum standards set by local and international bodies and specialists with respect to the following components: 1) PE Curricular Programs, both general education and degree-granting: 2) PE Facilities & Equipment; 3)Teacher Characteristics and Academic Qualifications: and, 4) Teaching Competencies in the domains of content knowledge. pedagogical skills, and professional skills. This study also delved into the problems and issues confronting the PE teachers and department heads of PE program. An action plan geared towru·ds the enhancement of the PE programs was formulated based on the findings of the study. The descriptive-quantitative design was utilized. The sample HEis totaled ten (10) and were drawn through purposive sampling based on the offering of degree-granting PE programs. Results of the study showed that the PE curricular program for both the general education and the degree-granting and teachin; competencies of teachers were generally satisfactory and met tne minimum standards required by the CHED and ICHPER.SD. The other two program components, i.e. teacher characterisbics and qualifications, and PE facilities and equipment were rated poor wnich signified that the HEis failed to meet the minimum requirements set by the aforementioned bodies and by local and foreign PE specialists.